Multifarious Indigenous Diazotrophic Rhizobacteria of Rice (Oryza sativa L.) Rhizosphere and Their Effect on Plant Growth Promotion - Mir, Mohammad Imran; Hameeda, Bee; Quadriya, Humera; Kumar, B. Kiran; Ilyas, Noshin; Kee Zuan, Ali Tan; El Enshasy, Hesham Ali; Dailin, Daniel Joe; Kassem, Hazem S.; Gafur, Abdul; Sayyed, R. Z. (Frontiers in Nutrition, 2022)
A diverse group of rhizobacteria persists in the rhizospheric soil, on the surface of roots, or in association with rice plants. These bacteria colonize plant root systems, enhance plant growth and crop yield. Indigenous rhizobacteria are known to promote soil health, grain production quality and serve as sustainable bioinoculant. The present study was aimed to isolate, identify and characterize indigenous plant growth-promoting (PGP) diazotrophic bacteria associated with the rhizosphere of rice fields from different areas of Jammu and Kashmir, India. A total of 15 bacteria were isolated and evaluated for various PGP traits, antagonistic activity against phytopathogens, production of hydrolytic enzymes, and biofilm formation under in-vitro conditions. The majority of the isolated bacteria were Gram-negative. Out of 15 bacterial isolates, nine isolates produced IAA (12.24±2.86 to 250.3±1.15 μg/ml), 6 isolates exhibited phosphate solubilization activity (36.69±1.63 to 312.4±1.15 μg/ml), 7 isolates exhibited rock phosphate solubilization while 5 isolates solubilized zinc (10-18 mm), 7 isolates showed siderophore production, 8 isolates exhibited HCN production, 6 isolates exhibited aminocyclopropane-1-carboxylate )ACC) deaminase activity, 13 isolates exhibited cellulase activity, nine isolates exhibited amylase and lipase activity and six isolates exhibited chitinase activity. In addition, 5 isolates showed amplification with the nifH gene and showed a significant amount of nitrogenase activity in a range of 0.127-4.39 μmol C2H4 mg−1 protein h−1. Five isolates viz., IHK-1, IHK-3, IHK-13, IHK-15, and IHK-25 exhibited most PGP attributes and successfully limited the mycelial growth of Rhizoctonia solani and Fusarium oxysporum in-vitro. All the five bacterial isolates were identified based on morphological, biochemical, and 16S rDNA gene sequencing study, as Stenotrophomonas maltophilia, Enterobacter sp., Bacillus sp., Ochrobactrum haematophilum, and Pseudomonas aeruginosa. Rice plants developed from seeds inoculated with these PGP strains individually had considerably higher germination percentage, seed vigor index, and total dry biomass when compared to control. These findings strongly imply that the PGP diazotrophic bacteria identified in this work could be employed as plant growth stimulators in rice.